Paediatric sickle cell disease at a tertiary hospital in Malawi: a retrospective cross-sectional study - Tsung-Shu Joseph Wu; Chikondi Sharon Chimbatata; Master RO Chisale; Alfred Bornwell Kayira; Frank Watson Sinyiza; Balwani Chingatichifwe Mbakaya; Paul Uchizi Kaseka; Pocha Kamudumuli (BMJ Publishing Group, 2021)
Introduction Sickle cell disease (SCD) remains a major cause of childhood mortality and morbidity in Malawi. However, literature to comprehensively describe the disease in the paediatric population is lacking.Methods A retrospective review of clinical files of children with SCD was conducted. Descriptive statistics were performed to summarise the data. χ2 or Fisher's exact test was used to look for significant associations between predictor variables and outcome variables (case fatality and length of hospital stay). Predictor variables that were significantly associated with outcome variables (p≤0.05) in a χ2 or Fisher's exact test were carried forward for analysis in a binary logistic regression. A multivariable binary logistic regression was used to identify covariates that independently predicted length of hospital stay.Results There were 16 333 paediatric hospitalisations during the study period. Of these, 512 were patients with SCD representing 3.1% (95% CI: 2.9%- 3.4%). Sixty-eight of the 512 children (13.3%; 95% CI: 10.5% - 16.5%) were newly diagnosed cases. Of these, only 13.2% (95% CI: 6.2% - 23.6%) were diagnosed in infancy. Anaemia (94.1%), sepsis (79.5%) and painful crisis (54.3%) were the most recorded clinical features. The mean values of haematological parameters were as follows: haemoglobin (g/dL) 6.4 (SD=1.9), platelets (×109/L) 358.8 (SD=200.9) while median value for white cell count (×109/L) was 23.5 (IQR: 18.0-31.2). Case fatality was 1.4% (95% CI: 0.6% - 2.8%)and 15.2% (95% CI: 12.2% -18.6%) of the children had a prolonged hospital stay (>5 days). Patients with painful crisis were 1.7 (95% CI: 1.02 - 2.86) times more likely to have prolonged hospital stay than those without the complication.Conclusion Anaemia, sepsis and painful crisis were the most common clinical features paediatric patients with SCD presented with. Patients with painful crisis were more likely to have prolonged hospital stay. Delayed diagnosis of SCD is a problem that needs immediate attention in this setting. Although somewhat encouraging, the relatively low in-hospital mortality among SCD children may under-report the true mortality from the disease considering community deaths and deaths occurring before SCD diagnosis is made.